THE EFFECTIVENESS DIFFERENCES OF CANANGA AROMATHERAPY AND JAVA LANGGAM MUSIC ON BLOOD PRESSURE OF THE ELDERLY WITH HYPERTENSION IN BPSTW YOGYAKARTA - Kurniasih, Dwi Endah; Erwanto, Rizky (Jurnal Keperawatan Respati Yogyakarta, 2021)
Elderly encounter decreased body functions, including cardiovascular function. The cardiovascular issue in elderly is hypertension. One of the non-pharmacological managements for hypertension is through the intervention of cananga aromatherapy and java langgam music. Quasi experiment with a control group design approach is the research method. The researcher divided two groups, namely cananga aromatherapy and java langgam music intervention groups. Interventions were given 4 times a week for two weeks. The researcher conducted Repeated Measure ANOVA and Friedman statistic tests for 3 measurement periods, while also performed independent t-test and Mann Whitney test to compare the both groups. The acquired results show that cananga aromatherapy can lower systolic blood pressure significantly (p-value: 0.007), while the java langgam music can lower systolic and diastolic blood pressures significantly (p-value: 0.000). There were disparities between systolic and diastolic blood pressures on both groups during the first week of the intervention (p-value: <0.05). The java langgam music intervention was more effective in lowering the blood pressure in elderly compared to cananga aromatherapy intervention. Keywords: Cananga aromatherapy; java langgam music; elderly with hypertension